Project of using low-potential energy sources at the Bratsk hydro power plant - V. D. Yurovskaya; S. V. Latushkina (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. Improving the energy efficiency of a hydroelectric power plant (HPP). Determination of the volume of lost thermal energy from HPP equipment. Development of options for the beneficial use of low-grade heat. Economic evaluation of the proposed options. Selection of the most appropriate waste heat utilization option. METHODS. The methods of the theory of heat and mass transfer, thermodynamic analysis, technical and economic calculations in the energy sector are used in the work. RESULTS. The article determined the temperatures of heat carriers in the cooling system of the hydroelectric generator of the Bratsk HPP. Calculated heat losses in the amount of 92,52 MW. 3 variants of heat supply for the facilities of the Bratsk HPP have been laid. An optimized scheme of heat generation using a heat pump installation (HPI) has been developed. A feasibility study of the proposed options for heat supply has been carried out. An analysis of the Russian HPI market was carried out. A cost-effective heat supply option with 2 Viesmann Vitocal 350-G Pro HPI was selected for implementation with a capital investment 34,46 million of RUB and a payback period of 7,3 years. CONCLUSION. The results of technical and economic calculations show the feasibility of introducing a HPI into the heat generation system of the Bratsk HPP.